Oxidative Stress Biomarkers and Quality of Life Are Contributing Factors of Muscle Pain and Lean Body Mass in Patients with Fibromyalgia - dos Santos, Jousielle Márcia; Rodrigues Lacerda, Ana Cristina; Ribeiro, Vanessa Gonçalves César; Scheidt Figueiredo, Pedro Henrique; Fonseca, Sueli Ferreira; da Silva Lage, Vanessa Kelly; Costa, Henrique Silveira; Pereira Lima, Vanessa; Sañudo, Borja; Bernardo-Filho, Mário; da Cunha de Sá Caputo, Danúbia; Mendonça, Vanessa Amaral; et al. (Biology, 2022)
(1) The evidence points to an increase in oxygen reactive species as one of the possible causes of fibromyalgia (FM). In addition, it is plausible that an imbalance in redox markers can be associated with pain amplification and dynapenia in FM patients. The aim of our study was to investigate possible factors associated with muscle pain and lean body mass in FM patients. (2) Methods: This was a quantitative, exploratory and cross-sectional study of 47 patients with FM (53.45 + 7.32 years). We evaluated self-perceptions of muscle pain, lean body mass, body composition, quality of life, sleep quality, depression index, muscle performance and oxidative stress biomarkers. (3) Results: We observed that lower blood levels of antioxidants and poor quality of life explained 21% of the greater muscle pain. In addition, high blood levels of oxidative stress, worse muscle performance and poor quality of life explained 27% of the lower lean mass in patients with FM. (4) Conclusions: Larger amounts of lipid peroxidation and reductions in antioxidant levels, in addition to lower muscle performance and poor life quality, are possible independent contributors to greater muscle pain and lower lean body mass in FM patients.
Number: 6
Keywords: TBARS; fibromyalgia; lean body mass; muscle pain; oxidative stress; quality of life; superoxide dismutase